The ratib samman ritual and its social function in the Sei Paham community, Sei Kepayang district (International Journal of Culture and Art Studies, 2025)
The Ratib Samman ritual is a highly popular tradition among the people of Sei Paham, Sei Kepayang District, and it has socially important functions. The purpose of this research is to reveal the social function of the Ratib Samman Ritual of Sei Paham Community, Sei Kepayang District. This research method is qualitative with data collection techniques through interviews, observations and document studies. Research activities are directed to find social facts that are happening in accordance with existing reality. The results of the study show that the community does not know when this ritual is interpreted as a practice of zikr and to get closer to oneself. Zikr as a Religious Tradition and Art in Sei Kepayang Village. The social function of the Ratib Samman ritual is as a form of solidarity and social integration, as well as a means of overcoming various problems that arise in the form of epidemics or diseases, famine, crime, and disturbances from supernatural beings.